The Influence of Risk Perception, Self-Efficacy, Investment Motivation, and FOMO on Crypto Investment Decisions - Kenanga Kenanga; Sutrisno Sutrisno (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to examine the influence of risk perception, self-efficacy, investment motivation, and Fear of Missing Out (FoMO) on cryptocurrency investment decisions among investors in Indonesia. A quantitative research approach was employed, with primary data collected through an online questionnaire. The study involved 190 respondents, the majority of whom were university students, accounting for 93.7% of the sample. Data were analyzed using multiple linear regression with IBM SPSS Statistics software. The results indicate that self-efficacy, investment motivation, and FoMO have a positive and significant effect on cryptocurrency investment decisions. In addition, risk perception was also found to have a positive and significant effect on cryptocurrency investment decisions. Simultaneously, all four independent variables significantly influence cryptocurrency investment decisions. These findings suggest that investment decision-making in highly volatile digital assets is not driven solely by financial considerations but is shaped by a complex interaction of cognitive, motivational, and emotional factors. Therefore, cryptocurrency trading platforms are encouraged to enhance investor education, improve transparency regarding investment risks, and provide financial literacy programs to support more rational and responsible investment decisions among retail investors.